Linear regression analysis - Seber, George Arthur Frederick (Wiley series in probability and statistics / Walter A. Shewhart / Samuel S. Wilks, 2003)
For more than two decades, the First Edition of Linear Regression Analysis has been an authoritative resource for one of the most common methods of handling statistical data. There have been many advances in the field over the last twenty years, including the development of more efficient and accurate regression computer programm, new ways of fitting regressions, and new methods of model selection and prediction. Linear Regression Analysis. second edition, revises and expands this standard text, providing extensive coverage of state-of-the-art theory and applications of linear regression analysis.